Energy Analysis and Process Simulation for the Energy Efficiency Improvement of Existing Chemical Plants; Chemical Engineering Transactions; Vol. 86 - Dyudnev V. Vyacheslav; Korotkii V. Vitalii; Novgorodtsev S. Stanislav; Boldyrev S. Stanislav; Pretoro A. Di Alessandro; Bragina Ju. Julia; Trusova M. E. Marina Evgenievna; Manentic F. Flavio (2021, 2021)
Title screen